Investigation on the Tunable-Length Zinc Oxide Nanowire Arrays for Dye-Sensitized Solar Cells - Shou-Yi Kuo; Ming-Yang Hsieh; Hsin-I Lin (International Journal of Photoenergy)
We had successfully fabricated ZnO-based nanowires by vapor transport method in the furnace tube. ZnO nanowire arrays grown in 600°C for 30 minutes, 60 minutes, 90 minutes, and 120 minutes had applied to the dye-sensitized solar cells. The dye loading is proportional to the total equivalent surface area of ZnO nanowire arrays in the cells and plays an important role in improving power conversion efficiency. The highest efficiency was observed in DSSC sample with ZnO nanowires grown for 90 minutes, which had the largest equivalent surface area and also the highest dye loading. According to our experimental results, the enhancement in power conversion efficiency is attributed to the higher light harvesting and reduction of carrier recombination. In addition, ZnO nanowires also contribute to the photocurrent in the UV region.